COVID-19 spike polypeptide vaccine reduces the pathogenesis and viral infection in a mouse model of SARS-CoV-2 - Hisham, Yasmin; Seo, Sun-Min; Kim, Sinae; Shim, Saerok; Hwang, Jihyeong; Yoo, Eun-Seon; Kim, Na-Won; Song, Chang-Seon; Jhun, Hyunjhung; Park, Ho-Young; Lee, Youngmin; Shin, Kyeong-Cheol; et al. (Frontiers in Immunology, 2023)
The SARS-CoV-2 coronavirus, which causes a respiratory disease called COVID-19, has been declared a pandemic by the World Health Organization (WHO) and is still ongoing. Vaccination is the most important strategy to end the pandemic. Several vaccines have been approved, as evidenced by the ongoing global pandemic, but the pandemic is far from over and no fully effective vaccine is yet available. One of the most critical steps in vaccine development is the selection of appropriate antigens and their proper introduction into the immune system. Therefore, in this study, we developed and evaluated two proposed vaccines composed of single and multiple SARS-CoV-2 polypeptides derived from the spike protein, namely, vaccine A and vaccine B, respectively. The polypeptides were validated by the sera of COVID-19-vaccinated individuals and/or naturally infected COVID-19 patients to shortlist the starting pool of antigens followed by in vivo vaccination to hACE2 transgenic mice. The spike multiple polypeptide vaccine (vaccine B) was more potent to reduce the pathogenesis of organs, resulting in higher protection against the SARS-CoV-2 infection.